New Insights Into the Peculiar World of the Shepherd-Dog Parasites: An Overview From Maremma (Tuscany, Italy) - Morandi, Benedetto; Mazzone, Angelica; Gori, Francesca; Alvarez Rojas, Cristian A.; Galuppi, Roberta; Deplazes, Peter; Poglayen, Giovanni (Frontiers in Veterinary Science, 2020)
Several developments have been recently achieved to deeply understand pet-dog parasites and their relationship with hosts; however, parasites’ presence and distribution in shepherd-dog have been mainly neglected. This gap appears serious, as shepherd-dogs could harbour zoonotic helminths including Echinococcus granulosus “sensu lato”. The related human disease, Cystic Echinococcosis, is a worldwide neglected disease, with high endemicity in the Mediterranean Basin. To evaluate the presence of Echinococcus granulosus and other parasites, a sheep-dog population from the province of Grosseto has been investigated. Overall, 648 dog fecal samples collected from 50 quite modern sheep farms, having a total of 216 dogs, were collected. Specimens were analyzed using a standardized centrifugal floatation method (specific gravity=1.3). Taeniid eggs eventually detected was followed by further egg isolation using a sieving/floatation technique. Eggs underwent DNA extraction, PCR and sequence analyses for species identification (gene target: 12S rRNA and nad1). Based on farm-level, 78% resulted positive to at least one parasite species or genus. The most represented intestinal helminths groups were Toxocara spp. in 64% of farms, followed by Ancylostomatidae eggs (58%), Trichuris vulpis (50%), Capillaria spp. (34%) and taeniid eggs (32%). Sequence analyses confirmed Taenia hydatigena presence in 7 farms, Taenia (syn. Multiceps) multiceps in 5 farms and T. pisiformis in one farm. No DNA was extracted from four previously taeniid egg positive farms. Results did not reveal the presence of E. granulosus in the investigated farms. Spearman’s test showed a positive corralation between flock size and the number of dogs per farm (ρ= 0.588, P<0.001). Quantitative analysis reported that the home slaughter practice was neither affected by the flock size nor by the number of dogs per farm. The probability to diagnose positive farms to taeniids had been increased of about 35% for each dog unit increase (OR=1.35, P=0.012). In conclusion, the widely spreading of T. hydatigena and T. multiceps clearly shows that dogs have still access to raw offal, a major risk for the transmission of E. granulosus. Being home slaughter an intelligible common practice, impending efforts must be implemented by the Public Health System in order to prevent and control zoonotic taeniids.